The Characteristics of Beaten and Unbeaten Mixed Tropical Hardwood Kraft Pulp - Nyoman J Wistara; Hotman Effendi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2011)
In the present works, pulp fibers were fractionated with Bauer McNet fiber fractionators and were classified into long fiber (R30), short fiber (P30/R100) and fines (P100/R200). Water retention value (WRV), dimensions measurements and pulp viscosity of fibers were determined based on of the modified method of Thode et al. (1960), the standard method of SII 1883-1986 and TAPPI 230 om-94, respectively. The measurement of fiber dimensions were done on 200 individual fibers. The increase of short fiber fraction clearly indicated fiber shortening effect of beating process. Beating processes increased WRV of fines above that of long fiber fraction. Beating of pulp did not significantly change the derivative value of fibers, but significantly decreased pulp viscosity.Key words: fiber classification, fines, pulp beating, water retention value (WRV).